The missing balance in offering degrees: case study of the Senegalese Virtual University (SVU) - Mehdi Zouaoui; Hamid Abdallah el hirtsi; Housseyn Goudjili (Journal of North African Economies, 2025)
The aim of this study is to identify the main challenges faced by public policy makers when planning to offer university degrees. Since higher education has to deal ex-ante with the concept of performance, according to the new public management (NPM) theory, it is assumed that job creation and inclusiveness are the primary goals. The research addresses the question of how to enhance employability and inclusiveness among youth in future. To achieve this objective, a case study of the Senegalese Virtual University (SVU) during 2013-2022 was analyzed to derive some conclusions and recommendations. The main results of our study are as follows: Partnership between government and business (G to B) is crucial for the success of higher education strategies to mitigate the problem of unemployment. Curricula and courses offered by the Ministry of Higher Education must align with the market demands for employment.